Non-Contact Stable Arterial Pulse Measurement Using mmWave Array Radar - Fanglin Geng; Zhongrui Bai; Hao Zhang; Changyu Liu; Peng Wang; Zhenfeng Li; Lidong Du; Xianxiang Chen; Zhen Fang (Bioengineering)
Pulse signals can serve as important indicators of one’s cardiovascular condition. However, capturing signals with stable morphology using radar under varying measurement periods remains a significant challenge. This paper reports a non-contact arterial pulse measurement method based on mmWave radar, with stable signals achieved through a range–angle focusing algorithm. A total of six subjects participated in the experiment, and the results showed that, under different measurement times, the pulse morphology of the same body part for each subject had good consistency, reaching a correlation of over 0.84, and four selected pulse signs remained stable. This is a quantitative assessment revealing a high correlation in pulse morphology measured by radar over different periods. In addition, the influence of array size and measurement distance was analyzed, providing a reference of array selection for research work with different requirements. This work offers an effective reference framework for long-term pulse measurement using radar technology.